1996
DOI: 10.1164/ajrccm.153.3.8630547
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation in the aging human lung.

Abstract: Aging has been associated with diminished lung function and increased susceptibility to lung infection. To determine whether changes suggestive of immune dysregulation and inflammation appear in the lungs of clinically normal individuals as a function of advancing age, we performed bronchoalveolar lavage (BAL) on discontinuous age groups (20-36, 45-55, and 65-78 yr old) of clinically normal volunteer subjects. We measured immunoglobulin (IgG, IgA, IgM), albumin, interleukin-6 (IL-6), and interleukin-10 concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
3
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 35 publications
10
109
3
2
Order By: Relevance
“…The current data shows that inflammation in the larger airways is increased in the a 1 ATD subjects despite more using inhaled steroids (which would be expected to have a beneficial effect) [23] and the subjects being younger (which would also be associated with less inflammation in the larger airways) [31,32]. MPO concentrations were higher, as was the chemoattractant LTB 4 .…”
Section: Discussionmentioning
confidence: 61%
“…The current data shows that inflammation in the larger airways is increased in the a 1 ATD subjects despite more using inhaled steroids (which would be expected to have a beneficial effect) [23] and the subjects being younger (which would also be associated with less inflammation in the larger airways) [31,32]. MPO concentrations were higher, as was the chemoattractant LTB 4 .…”
Section: Discussionmentioning
confidence: 61%
“…The increased susceptibility of elderly to particulate matter may also be to due lifelong exposure to environmental substances that are harmful to health, as well as to previous respiratory infections, as observed by Meyer et al 35 in a study of healthy non-smokers from 65 to 78 years of age. The authors observed an increase in neutrophils, immunoglobulins (IgG, IgA, and IgM), and interleukin-6 (IL-6) in fluid from bronchoalveolar lavage, as compared to samples from individuals 20 to 36 years of age.…”
Section: Discussionmentioning
confidence: 89%
“…Focusing on studies on normal values, nine studies specifically designed to provide data on BAL cellular normal reference values in adult subjects, fulfilling the current literature search criteria, have been published as observational studies (table 2) [26, [28][29][30][31][32][33][34][35]. Eight of these were performed in North America and only one in Europe [35].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Most of the subjects were male, nonsmokers and aged ,50 yrs. Only four studies specifically evaluated the influence of age on BAL characteristics [26,[33][34][35], and most of the subjects concerned were nonsmokers. Since the vast majority of the studies were from North America, in particular the USA, it is not surprising that in some cases volunteers were reimbursed for participation.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%